2017
DOI: 10.1186/s12870-017-1192-2
|View full text |Cite
|
Sign up to set email alerts
|

Differential gene expression in response to Fusarium oxysporum infection in resistant and susceptible genotypes of flax (Linum usitatissimum L.)

Abstract: BackgroundFlax (Linum usitatissimum L.) is a crop plant used for fiber and oil production. Although potentially high-yielding flax varieties have been developed, environmental stresses markedly decrease flax production. Among biotic stresses, Fusarium oxysporum f. sp. lini is recognized as one of the most devastating flax pathogens. It causes wilt disease that is one of the major limiting factors for flax production worldwide. Breeding and cultivation of flax varieties resistant to F. oxysporum is the most eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 62 publications
2
34
0
3
Order By: Relevance
“…The average length of individual fibers obtained from mature plants ranged from 14.7 ± 2.0 mm in L. angustifolium to 21.5 ± 1.2 mm in Drakkar. The proportion of fibers longer SAM, shoot apical meristem (Zhang and Deyholos, 2016); cPAR, cortical parenchyma; iFIB, intrusively growing fibers (Gorshkova et al, 2018b); tFIBa, fibers depositing tertiary cell wall, earlier stage (Gorshkov et al, 2019); tFIBb, fibers depositing tertiary cell wall, later stage (Gorshkov et al, 2017); sXYLa, xylem part, the same segment of the stem as for tFIBa (Gorshkov et al, 2019); sXYLb, xylem part, the same segment of the stem as for tFIBb (Mokshina et al, 2020); LEAF, upper leaves from individual plants under normal conditions (Dmitriev et al, 2016); ROOT, root tips, average for control samples (Dmitriev et al, 2017). When calculating the FC, to avoid division by zero, +1 was added to all the TGR values.…”
Section: Expression Of Selected Genes In Samples From Various Flax Gementioning
confidence: 99%
See 1 more Smart Citation
“…The average length of individual fibers obtained from mature plants ranged from 14.7 ± 2.0 mm in L. angustifolium to 21.5 ± 1.2 mm in Drakkar. The proportion of fibers longer SAM, shoot apical meristem (Zhang and Deyholos, 2016); cPAR, cortical parenchyma; iFIB, intrusively growing fibers (Gorshkova et al, 2018b); tFIBa, fibers depositing tertiary cell wall, earlier stage (Gorshkov et al, 2019); tFIBb, fibers depositing tertiary cell wall, later stage (Gorshkov et al, 2017); sXYLa, xylem part, the same segment of the stem as for tFIBa (Gorshkov et al, 2019); sXYLb, xylem part, the same segment of the stem as for tFIBb (Mokshina et al, 2020); LEAF, upper leaves from individual plants under normal conditions (Dmitriev et al, 2016); ROOT, root tips, average for control samples (Dmitriev et al, 2017). When calculating the FC, to avoid division by zero, +1 was added to all the TGR values.…”
Section: Expression Of Selected Genes In Samples From Various Flax Gementioning
confidence: 99%
“…Flax is a bast fiber crop on which the most advanced molecular studies of fiber development have been conducted. The whole genome sequence of cultivated flax was assembled in 2012 (Wang et al, 2012), and was used for SNP (single nucleotide polymorphism) discovery (Kumar et al, 2012), transcriptomic profiling of different tissues (Dmitriev et al, 2016(Dmitriev et al, , 2017Zhang and Deyholos, 2016) and construction of a high resolution consensus map of flax that integrated genetic and physical data (Cloutier et al, 2012). These approaches considerably advanced the earlier important studies to large-scale molecular characterization of the flax genome and transcriptome (Day et al, 2005;Roach and Deyholos, 2007;Fenart et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…For each gene, the expression was evaluated on the basis of RNA-Seq data obtained for six varieties and populations of flax that were grown under control conditions or with Fusarium oxysporum isolate #39 (Dmitriev et al, 2017). Results are shown in Table 1, where log (CPM Fusarium/CPM control) values for each gene studied are presented for resistant (3896, 'Dakota', 3896 × AP5, 'Dakota' × AP5) and susceptible (TOST and AP5) genotypes under control conditions and 48 hours after inoculation with Fusarium oxysporum.…”
Section: Resultsmentioning
confidence: 99%
“…According to Diederichsen et al (2008) the experiment performed in Canada, where 153 flax accessions from 24 countries were evaluated, showed higher than average resistance to flax wilt, anthracnose and pasmo in accessions from East Asia, while germplasm from the Indian subcontinent showed considerably lower than average resistance; germplasm from North America and South America (mostly linseed) displayed above average resistance to flax wilt, while European accessions (mostly fibre flax) showed lower than average resistance to this disease. A study by Dmitriev et al (2017) has revealed that the mechanisms of flax response to flax wilt have been actively studied; however, the data on the plant response to infection and resistance gene candidates are currently very limited.…”
Section: Resultsmentioning
confidence: 99%